(untitled) (The Journal of Interdisciplinary Human Studies, 2026)
This article presents a comprehensive scientific analysis of “Madarik al-tanzil wa haqaʼiq al-taʼwil,” a Qurʼanic exegesis authored by Abu al-Barakat al Nasafi (d. 710/1310). The research examines the reasons for the composition of the work, its methodological framework, the primary sources employed by the author, and its significance within Sunni theological tradition. In addition, the article explores the relationship between this tafsir and the exegetical works “al-Kashshaf” by Mahmud al-Zamakhshari and “Anwar al-tanzil wa asrar al-taʼwil” by Nasir al-Din al-Baydawi, highlighting their influence on its scholarly and methodological structure. The study also provides an overview of manuscript copies of the tafsir, as well as commentaries and marginal glosses written on it, and discusses its place in contemporary academic research across Uzbekistan, Türkiye, Saudi Arabia, and Indonesia.